Aerobiology, aerodynamics and pollen sampling - Emberlin, Jean (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
Aerobiology is the interdisciplinary science focused on the study of airborne organisms and biological materials. Aerodynamics rules influence the transport of the pollens through the air and their eventual removal from the airflow. It depends on the various factors, such as pollen size, shape and weight and features of the air and weather. The most commonly used pollen sampling methods are volumetric traps, rotorod samplers and cyclones.